Superior vena cava syndrome: a case report of a rare form of presentation - Behera, Bijaya K.; K., Vishnu; George, Jaison; Nahak, Susanta K. (International Journal of Research in Medical Sciences, 2018)
Superior vena cava syndrome (SVCS) is the clinical manifestation of superior vena cava (SVC) obstruction, with severe reduction in venous return from the head, neck and upper extremities. It is a medical emergency. Obstruction to the SVC may be caused by neoplastic invasion of the venous wall associated with intravascular thrombosis or, more simply, by extrinsic pressure of a tumour mass against the relatively thin-walled SVC. More than 80% cases of SVCS are caused by malignant mediastinal tumours. We present a 42-year-old female patient who was admitted with 15 days history of swelling of face, neck and upper limbs and dyspnea of 5 days duration at MKCG Medical College Hospital, Berhampur, Odisha, India. The patient was diagnosed as a case of Non-Hodgkin's Lymphoma (NHL) which is a rare form of presentation. In this case report we would like to highlight that although lung carcinoma being the most common cause of acute superior vena cava syndrome, other malignancies like NHL should also be kept in mind and the importance of a detailed history, clinical examination and thorough investigations cannot be over emphasised.